TREN DAN TANTANGAN SELF-MEDICATION PADA KELUHAN RINGAN DI DAERAH PERBATASAN INDONESIA-MALAYSIA: STUDI LITERATUR KASUS DI KABUPATEN SAMBAS - Nurfiani, Suharti; Fajri, Mathla'il (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Self-medication is a common health behavior, especially for mild symptoms. This study reviews the trends and challenges of self-medication in Indonesia–Malaysia border areas, focusing on Sambas Regency. A descriptive-qualitative literature review was conducted based on 15 relevant scientific articles. The findings reveal that self-medication is influenced by limited access to healthcare services, low medication literacy, cultural norms, and weak drug distribution supervision. Commonly used drugs include analgesics, antipyretics, supplements, and traditional herbal remedies. The border context also facilitates access to cross-border medicines, raising concerns about quality and safety. This study highlights the urgency of implementing community-based health education, strengthening the role of community pharmacists, and developing adaptive and context-specific pharmaceutical policies in remote border regions.